The Concept of State Control over Forests and Forest Areas in Indonesia - Suparto, Suparto; Admiral , Admiral; Ardiansyah, Ardiansyah; Namazovna, Sultanova Dilshoda (Journal of Law, Environmental and Justice, 2025)
Constitutionally, the concept of a state's right to control forests and forest areas is public and exercised through administrative permits, but it is often misunderstood as an absolute right, which can lead to mismanagement and ecological damage. This research aims to describe the concept of state attributive control over forests and forest areas through standardized permitting instruments. This type of research is normative, employing a statutory approach to analyze the basic concept of the state's right to control, that outlined in Article 33 of the 1945 Constitution of the Republic of Indonesia and relevant Indonesian regulations. This research shows, first, that the error in distinguishing between the concepts of rights and permits in forest control reflects the misconception that state authority is absolute, whereas it is attributed to the public interest. Second, it's important to understand that permits are a way for the government to control forests, which is done through permits for using forest products, area use permits, and environmental services, as explained in the Forestry Law, the Omnibus Law, and other related regulations. With this concept, forest utilization permits are not merely administrative instruments, but rather social and ecological contracts that involve violations of environmental